Optimization of Mechanical Indices for Clinical Contrast‐Enhanced Ultrasound. (8th December 2020) - Piskunowicz, Maciej; Sridharan, Anush; Poznick, Laura; Silvestro, Elizabeth; Hwang, Misun
Abstract : The quality of contrast‐enhanced ultrasound (CEUS) imaging performed with high‐frequency convex and linear transducers is often suboptimal. A common solution to improving the microbubble signal is by increasing the volume of the ultrasound contrast agent being administered. An alternative technique to improve the signal from the contrast agent is to adjust the mechanical index (MI). This study aimed to compare the manufacturer's default MI to an optimal MI (as determined by the best contrast‐to‐tissue ratio) for improving the CEUS image quality using linear and convex transducers. This study found that in most cases, the default CEUS MI setting by the manufacturer is often suboptimal, and increasing the MI is necessary to improve the contrast‐to‐tissue ratio and image quality. The MI can be modified by the clinician during the study to improve the quality of the clinical CEUS examination.